Formulation Of Herbal Drug into Modern Dosage Form - Mali, Kavita; S. Chundawat, Lokendra; Soni, Rupesh; Gupta, Manish (Journal of Neonatal Surgery, 2025)
Herbal medicine, as defined by the World Health Organization (WHO), encompasses the use of herbs, herbal components, preparations, and finished products derived from botanical sources. These remedies are abundant in phytochemicals bioactive compounds such as saponins, flavonoids, glycosides, tannins, alkaloids, and terpenoids - which contribute to their diverse therapeutic effects. Herbal treatments are employed in the management of various health conditions, including gastrointestinal disorders, skin infections, inflammation, migraines, and fatigue. Compared to conventional pharmaceuticals, herbal medicines are generally associated with fewer side effects and greater affordability, enhancing their appeal and accessibility. Recent advancements in pharmaceutical technology have led to the development of novel herbal drug delivery systems such as transfersomes, ethosomes, microspheres, phytosomes, liposomes, polymeric nanoparticles, and nanocapsules that significantly improve the solubility, stability, bioavailability, and targeted delivery of herbal compounds. Among these innovations, phytosome technology stands out as a patented approach that combines herbal extracts with phospholipids to enhance absorption and therapeutic efficacy. These advanced systems not only optimize the pharmacological performance of herbal medicines but also ensure better protection of active ingredients against degradation. The integration of modern delivery technologies with traditional herbal remedies marks a significant evolution in the field, expanding the clinical utility and reinforcing the relevance of herbal medicine in modern healthcare. Ongoing research and development in this area hold promising potential for further innovations and broader therapeutic applications.